Analysis of the chemical profile of cerrado pear fixed compounds by mass spectrometry with paper spray and volatile ionization by SPME-HS CG-MS (Research, Society and Development, 2020)
Eugenia klotzschiana Berg is a native fruit of the cerrado, belonging to the Myrtaceae family, known as the cerrado pear and very little explored. The present study's objective was to obtain the profile of the fixed and volatile chemical constituents of the fruit. Mass spectrometry with ambient ionization paper spray (PS-MS) was used in positive and negative mode for fixed compounds. For volatiles, solid-phase microextraction by head space and gas chromatography was employed. The PS-MS identified 31 compounds, 21 in the negative and 10 in the positive mode, including fatty acids, flavonoids, phenolic acids, tannins and sugars. The solid-phase microextraction method was used in head space mode, using the polydimethylsiloxane-divinylbenzene fiber to extract volatile organic compounds (VOCs). The volatiles detected totaled 11 substances, belonging to the class of monoterpenes, sesquiterpenes, and esters. PS-MS was capable and efficient in determining the fixed compounds present in the cerrado pear pulp, providing the chemical profile of the fruit, which contains essential compounds with potential antioxidant bioactivity. The volatile profile was obtained with success, indicating menthol, fruity and vanilla notes in the pulp of the cerrado pear.